Peran Model Bisnis Dalam Internasionalisasi Perusahaan: Sebuah Eksplorasi Perusahaan Listrik Eropa Dalam Konteks Transisi Energi - Jeni Susyanti; Denilson Pereira Lay (JURNAL ILMIAH EKONOMI DAN MANAJEMEN, 2025)
This article ties in directly related to the growing attention toward the concept of business models in the context of international business (IB), using the energy transition as an empirical backdrop to examine its significance in the internationalization process of firms. The global transformation in the energy sector presents challenges for nearly all industries, though certain sectors face particularly substantial obstacles from an IB perspective. This study investigates a group of European companies that initially operated under stringent regulations and partial state ownership, until government-led market liberalization created opportunities for increased competition and broader international expansion. These companies were compelled to adapt their business models in response to the shifting landscape, while new entrants began penetrating the market by leveraging technologies and innovative business models in the energy sector.